Effect of Guava Leaf Infusion on Diarrhea Frequency at Kalirejo Public Health Center - Indah, Indah; Andora, Novika; Stiexs, Anggie (Genius Journal, 2025)
Introduction: Diarrhea remains a major public health concern in Indonesia, particularly in rural areas. It is commonly caused by consuming food or drinks contaminated with microorganisms. While conventional treatments such as oral rehydration solutions and zinc are widely used, traditional herbal remedies like guava leaves (Psidium guajava) are increasingly gaining attention due to their antidiarrheal properties. Objective: This study aimed to examine the effect of guava leaf infusion on reducing the frequency of diarrhea among patients at Kalirejo Public Health Center, Negeri Katon District, in 2024. Method: A quasi-experimental study was conducted with two groups: an intervention group receiving guava leaf infusion and a control group receiving standard care. Thirty diarrhea patients were selected using accidental sampling and divided equally into both groups. The frequency of diarrhea was recorded before and after treatment. Result: The intervention group showed a greater reduction in diarrhea frequency, from a mean of 7.33 to 5.47 episodes per day (mean reduction of 1.87). The control group experienced a smaller decrease from 7.07 to 6.20 episodes per day (mean reduction of 0.80). Statistical analysis revealed a significant difference between groups (ρ = 0.001), indicating the effectiveness of guava leaf infusion. Conclusion: Guava leaf infusion significantly reduces the frequency of diarrhea, supporting its use as an effective complementary therapy. It offers a natural, accessible, and low-cost treatment option, especially in areas with abundant guava plants. Further research is recommended to explore additional herbal remedies and underlying causes of diarrhea in similar settings.